Kesetaraan Gender pada Penyuluh Agama Islam dalam Melakukan Penguatan Komunikasi Pembangunan Agama di Kabupaten Simalungun Sumatera Utara - Rosyidatul Gultom (Medan Resource Center, 2021)
This research is entitled ‘Gender Equality in Islamic Religious councelors in strengthening Religious Development Communication in Simalungun Regency’. The theory use in this research is the Gender Role Theory proposed by Prof. Alice Eagly in 1987. The object of this research is a female Islamic religious instructor who strengthens communication on religious development in Simalungun Regency, North Sumatera. The method used in this research is descriptive analysiswith a qualitative approach. The analytical technique used in this research is using qualitative descriptive with data analysis by means of in-depth interviews. The result show that in Simalungun Regency, North Sumatera, Female religious instructors had the same important role as male religious instructor, that’s mean there is gender equality.